NCOA5 induces sorafenib resistance in hepatocellular carcinoma by inhibiting ferroptosis - Shuang Gao; Lulu Fan; Huiyan Wang; Anqi Wang; Mengyao Hu; Lei Zhang; Guoping Sun (Cell Death Discovery)
Abstract NCOA5 has been identified as a crucial factor in the progression of hepatocellular carcinoma (HCC). This study investigates the expression of NCOA5 in HCC, revealing its significant overexpression in tumor tissues compared to healthy liver tissues, as evidenced by analysis of the TCGA dataset and RT-qPCR in patient samples. Higher NCOA5 levels correlate with poor overall survival, highlighting its role as a prognostic indicator. Furthermore, our findings suggest that elevated NCOA5 is associated with resistance to sorafenib, a common chemotherapeutic agent for HCC, as shown through analysis of publicly available datasets and the establishment of sorafenib-resistant HCC cell lines. Mechanistically, NCOA5 appears to inhibit ferroptosis in HCC cells by modulating glutathione peroxidase 4 (GPX4) levels. Knockdown of NCOA5 sensitizes resistant cell lines to sorafenib and induces ferroptosis by decreasing GPX4 expression. Additionally, NCOA5 regulation of GPX4 is mediated through the transcription factor MYC. In vivo studies further validate that targeting NCOA5 enhances the efficacy of sorafenib in resistant HCC models by promoting ferroptosis. Collectively, these findings underscore the potential of NCOA5 as a therapeutic target to overcome drug resistance in HCC, providing insights into its role in modulating treatment responses and patient prognosis.